Validação lingüística dos questionários de qualidade de vida em fibrose cística Linguistic validation of cystic fibrosis quality of life questionnaires - Tatiana Rozov; Maristela T. Cunha; Oliver Nascimento; Alexandra L. Quittner; José R. Jardim (Elsevier, 2006)
OBJETIVO: O propósito deste estudo foi validar em português as quatro versões de questionários de qualidade de vida em fibrose cística, desenvolvidos para pacientes com fibrose cística de 6 a 11 anos, de 12 a 13 e mais de 14 anos, e para os pais de pacientes de 6 a 13 anos. MATERIAL E MÉTODOS: A validação das quatro versões de questionários de qualidade de vida em fibrose cística (de 35 e 50 questões, abrangendo nove domínios) constou de: versão inglês-português, aplicação-piloto, tradução retrógrada e aprovação da autora da versão inglesa. As quatro versões foram aplicadas a 90 pacientes estáveis (30 de cada grupo etário) e aos pais de doentes de 6-13 anos (n = 60), em duas entrevistas, com intervalo de 13-17 dias. Foi avaliada a reprodutibilidade pelo coeficiente de correlação intraclasse (CCI). O estudo foi aprovado pela comissão de ética em pesquisa da instituição. RESULTADOS: A reprodutibilidade foi boa (CCI = 0,62 a 0,99) para as quatro versões, em todos os domínios, exceto o digestivo (CCI = 0,59 e CCI = 0,47) para os grupos etários de 6 a 11 e 12 a 13 anos, respectivamente, e domínio papel social (CCI = -0,19 ) para o grupo acima de 14 anos. CONCLUSÃO: A tradução e a adaptação à língua e à cultura brasileiras das quatro versões de questionários de qualidade de vida em fibrose cística mostraram-se de fácil entendimento e boa reprodutibilidade. OBJECTIVE: The purpose of this study was to validate the Portuguese translations of four cystic fibrosis quality of life questionnaires (CFQ). The first three were developed for patients with cystic fibrosis aged from 6 to 11 years, from 12 to 13 years and 14 years or more, while the fourth was developed for the parents of patients aged 6 to 13 years. MATERIAL AND METHODS: The four CFQ translations contained from 35 to 50 questions covering nine domains and were validated as follows: translation from English to Portuguese, pilot application, back translation and then approval by the author of the English versions. The four translations were applied to 90 stable patients (30 from each age group) and the parents of patients aged 6-13 years (n = 60), on two occasions with a 13 to 17 day interval. Intraclass Correlation Coefficients (ICC) were used to measure reproducibility. This study was approved by the Commission for Ethics in Research at the institution. RESULTS:Reproducibility was good (ICC = 0.62 to 0.99) for the four translations in all domains, with the exceptions of the Digestion domain for the 6 to 11 and 12 to 13 years age groups with ICC = 0.59 and 0.47, respectively and the Social Role domain for the 14 and over age group (ICC = -0.19 ) CONCLUSION: The translation and cultural adaptation for Brazil resulted in four CFQ versions that are easy to understand and offer good reproducibility.